Identification of biofilm-forming Escherichia coli in dressed chickens from a selected slaughterhouse in Calamba City, Laguna - Santamaria, Janyll Helaena D.; Talagtag, Maxine E.; Ventanilla, Yuan L.; Zialcita, Althea Brianna O.; Roxas, Evalyn A.; Ramos-Mortel, Buenalyn Teresita M. (Manila College of Public Health, University of the Philippines Manila, 2024)
Background
E. coli is known for its role in propagating antimicrobial resistance (AMR) and its biofilm-forming capability. AMR is one of the top global public health challenges of the 21st century. Apart from the clinical setting, AMR within the agricultural sector is relevant due to the risk of persistent infections in humans and animals. Biofilm formation, a bacterial survival mechanism, contributes to AMR primarily through recalcitrance and horizontal gene transfer. There is, however, a lack of research investigating biofilm formation among broiler chickens at the slaughterhouse level. This study aimed to investigate the presence, the antimicrobial susceptibility profile, and the biofilm-forming capability of E. coli from broiler chickens in a selected slaughterhouse from Calamba City, Laguna.

Methods
This descriptive, quantitative study utilized 40 dressed chicken samples from 20 farms in four provinces from Region IV-A that delivered to the slaughterhouse. 38 E. coli isolates obtained from chicken leg meat and cecum were processed for identification and antimicrobial susceptibility testing (AST) using VITEK® 2. The isolates were subjected to phenotypic tests for biofilm formation, namely the Congo Red agar (CRA) and tissue culture plate (TCP) methods.

Results
High resistance rates were observed against ampicillin (92.11%) and trimethoprim-sulfamethoxazole (65.79%). Among the cecum isolates, resistance was noted against ciprofloxacin (42.11%). Intermediate susceptibility was seen against colistin (84.21%). MDR E. coli was also detected (52.63%). Biofilm-forming E. coli was detected through the CRA method (26.32%) and the TCP method (44.74%). 17 out of 18 biofilm-forming isolates detected by the TCP method were AMR E. coli.

Conclusion
To the researchers' knowledge, this is the first study that identified biofilm formation in E. coli obtained from chickens-at-slaughter in the Philippines. The findings of this study highlighted the double burden of resistance among bacteria and biofilm formation that contributes to AMR in humans, animals, and the environment. Guided by the One Health approach, active surveillance and strategies to address AMR and biofilm formation should be implemented to safeguard public health.
Includes references and appendices.
Special Study
Keywords: Escherichia coli -- Biofilms -- Philippines -- Calamba City; Chickens -- Contamination -- Philippines -- Calamba City; Meat -- Microbiology -- Philippines -- Calamba City; Food -- Contamination -- Philippines -- Calamba City; Calamba City (Philippines) -- Slaughterhouses -- Hygiene